Motoric Game-Based Learning Model to Grow Character Values “GOROMAN” (Cooperation and Independent) Elementary School 190, Gresik District - Sunanto; Mariati, Pance; Muchamad Samsul Huda; Didik Purwanto (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Abstract: Regarding the problem and the focus of assistance from the findingsobtained in the field and peer discussions with teachers still focus on physics in learning physical education at schoolbase. Physical education is not only a physical focus, but character values ​​are also given to students in the learning process. Physical education and sports are based on methodsgame motor skills to grow character The method used in this activity is a model of filling out questionnaires, materials, discussions, game simulations and evaluations. While the discussion of the results of the service includes peer discussions that are relevant to the findings of the mentoring results found to be includedcategory understand the importance of character education given to students in gamesmotor to foster the value of mutual cooperation and independence.